PHYTOCHEMICAL, ETHNOMEDICINAL AND PHARMACOLOGICAL POTENTIALS OF SEABUCKTHORN- A MINI REVIEW - SIVARAJ ANBARASU,; MANIKKAM RADHAKRISHNAN,; ARMUGAM SURESH,; JERRINE JOSEPH, (International Journal of Pharma and Bio Sciences, 2015)
Sea Buckthorn (SBT) is distributed in the plains of India. The plant parts are used traditionally for several ailments. Medicinally, it has been proven to possess various pharmacological activities such as antioxidant, antimicrobial, antifungal, metabolic disorders, immunostimulatory activity, hepatoprotectant and anticancer activity. Several studies reveal the presence of various phytochemical constituents viz., flavonoids (isorhamnetin, quercetin, myricetin, kaempferol and their glycoside compounds), carotenoids (β and δ-carotene, lycopene, Zeaxanthin), few essential amino acids, sitosterol, triterpene, fatty acids, tannin acid, 5-hydroxytryptamine, umbelliferone, antioxidant vitamins and minerals in various parts of SBT. These studies reveal that SBT is a potential source of medicinally active compounds and have various pharmacological effects; yet the anti mycobacterial activity of this plant is unexplored and not well documented to the best of our knowledge, research in this area will encourage finding therapeutic use for TB patients which will be a next wonder drug as hepatoprotectant, immunostimulatory as well as anti microbial.